Perbandingan Kadar Flavonoid Total Ekstrak Daun Sambung Nyawa (Gynura procumbens L.) dari Simplisia dengan Metode Pengeringan yang Berbeda - Minda Warnis; Ellen Angelina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The sambung nyawa leaf (Gynura procumbens L.) is a simplicia that has various properties. One of the chemical compounds in the leaves that have medicinal properties is flavonoids. Flavonoid compounds in sambung nyawa leaves have benefits as antihypertensive, antioxidant, antihyperglycemic, and anti-inflammatory. The difference in the simplicia drying method had an effect on the total flavonoid content contained in the extract. The aim of the study was to measure the total flavonoid content of sambung nyawa leaf extract from simplicia dried by wind drying and oven drying at 40°. The research method is an experimental study by measuring the total flavonoid content of the extracts of sambung nyawa leaves from wind-dried and oven-dried simplicia using UV-Vis Spectrophotometry. The results showed that the total flavonoid content of the extract from the wind-dried sambung nyawa was 42.64 mg/g and 40°C oven-dried was 50.14 mg/g. It was concluded that sambung nyawa leaves dried in an oven at 40°C produced extracts with higher total flavonoid content than wind-dried simplicia.